Sentidos-e-significados de professores de diferentes áreas sobre a Proposta Curricular e os Cadernos da SEE/SP - Anjos, Arlete Alves dos (2011)
This research aims at investigating the senses-and-meanings of teachers from different areas of the curriculum on the Proposta Curricular [Curricular Proposal] and the Cadernos do Professor e do Aluno [Teachers and Students Notebooks] material that is published and distributed by the São Paulo State Education Department as well as their use in the classroom. This study is based on the Socio-Cultural-Historical Theory (Vygotsky, 1934/1998-2001; 1934-1991) and discusses the following key theoretical constructs: teaching-learning and development (Vygotsky, 1934-2001, Newman and Holzman, 2002), emotions (Vygotsky, 1926/2004; 1934-1998; Aguiar, 2001), senses-and-meanings (Vygotsky, 1925-2004; 1934-2001; Aguiar, 2001/2006, Lessa, 2011), language (Vygotsky, 1934-2001, Lacoste, 1998). The study is also based on the concepts of prescribed work and accomplished work (Amigues, 2004; Souza-e-Silva, 2004); local and global knowledge (Canagarajah, 2005), practical and instituted types of knowledge (Souza-e-Silva, 2008, Schwartz, 2007) and on official documents that guide the English teachers practices in the educational context (São Paulo, 2008; Brasil, 1998). Public school teachers from different areas namely: Languages, History and Mathematics - took part in this research. The research methodology used was the interpretive methodology (Moita Lopes, 1996; Erickson, 1986, among others), and data collection was carried out by means of audio recorded interviews - the initial interview was semi-structured (Rizzini, Castro and Sartor, 1999). For data analysis and interpretation, the category of senses-and-meanings was used. Results obtained reveal that the Curricular Proposal meets the expectations of teachers in terms of the content established for all the school years. The research also revealed that teachers renormalize the methodological guidelines prescribed in the above cited Notebooks. In order to carry out these renormalizations, the teachers support their actions on their local knowledge and their professional experience. In summary, one can say that the teachers senses-and-meanings about the Notebooks Proposal are built on the dialectical relationship that is established between that which is prescribed and their own pedagogical practices